Biological parameters of Proprioseiopsis iorgius on Tetranychus desertorum (Acari: Phytoseiidae, Tetranychidae) - TELLO-MERCADO, VÍCTOR; BRICEÑO-VALDIVIA, ROMINA; CASTILLO-MARTÍNEZ, PAMELA (Revista Colombiana de Entomología, 2011)
The postembryonic development, consumption and life table parameters of Proprioseiopsis iorgius were studied at 23±3°C and 70±51% RH and a photoperiod of 14:10 h (L:D) in order to evaluate the potential of this predator for feeding on the desert spider mite Tetranychus desertorum. Eggs, nymphs, larvae and adults of T. desertorum could be considered optimal food for P. iorgius, because the survival rate was 100%, 96%, 93% and 93%, respectively. The duration of postembryonic development of P. iorgius was significantly different (p<0.05) between the distinct diets; the larval stage was the shorter duration (1.2 to 1.3 days) even though it did not feed on any stage of T. desertorum. The oviposition and postoviposition periods and longevity of P. iorgius were 11.2, 3.0 and 16.8 days, respectively. Biological parameters of P. iorgius and T. desertorum were: rm=0.225 and 0.191; T=14.961 and 18.565; R0=28.913 and 34.357, λ=1.252 and 1.210, respectively. The high values of rm and λ found for P. iorgius under the experimental conditions are indicators of the control potential that this phytoseiid mite could have as a predator of T. desertorum.